Cages Sanitation and Health Complaints Among Dairy Farmers in Murukan Village, Jombang - Rizqi Zuroida (JURNAL KESEHATAN LINGKUNGAN, 2018)
Dairy farmers have risk to get bad effect from dairy cows waste that is not managed properly, because dairy farmers use to make a contact with dairy cows waste everyday. Dairy cows waste contains various microorganism, gases and other organic materials that can be an agent of disesase in humans. Objectives of this study were to analyze the correlation between cages sanitation that include location of the cages, cage's construction building, cleanliness of the cage and density of flies with dairy farmer's health complaints during work in the cages. This was an observational study with cross-sectional approach. Sampling was done by using simple random sampling method. The sample size used in this study was 58 dairy farmers that interviewed about their health complaints during work in the cages and observed the cages. The cages sanitation was sufficient (70,7%), while the density of flies around the cages was medium category (48,3%). Result of this study showed that there was no correlation between cages sanitation with dairy farmer's health complaints during work in the cages (p=0,710). Dairy farmers should pay more attention and improve their cages sanitation especially in maintaining cleanliness of the cages, so that health complaints can be minimized.